Cert Prep: Certified SOLIDWORKS Associate. - Corbett, Gabriel (linkedin.com, 2015)
Prepare for the Certified SOLIDWORKS Associate (CSWA) exam, and master the techniques necessary to design parts and assemblies with the core features in SOLIDWORKS.